Adaptive divergence in shell morphology in an ongoing gastropod radiation from Lake Malawi - Van Bocxlaer, Bert (BMC Evol Biol, 2020)
BACKGROUND: Ecological speciation is a prominent mechanism of diversification but in many evolutionary radiations, particularly in invertebrates, it remains unclear whether supposedly critical ecological traits drove or facilitated diversification. As a result, we lack accurate knowledge on the drivers of diversification for most evolutionary radiations along the tree of life. Freshwater mollusks present an enigmatic example: Putatively adaptive radiations are being described in various families, typically from long-lived lakes, whereas other taxa represent celebrated model systems in the study of ecophenotypic plasticity. Here we examine determinants of shell-shape variation in three nominal species of an ongoing ampullariid radiation in the Malawi Basin (Lanistes nyassanus, L. solidus and Lanistes sp. (ovum-like)) with a common garden experiment and semi-landmark morphometrics. RESULTS: We found significant differences in survival and fecundity among these species in contrasting habitats. Morphological differences observed in the wild persisted in our experiments for L. nyassanus versus L. solidus and L. sp. (ovum-like), but differences between L. solidus and L. sp. (ovum-like) disappeared and re-emerged in the F(1) and F(2) generations, respectively. These results indicate that plasticity occurred, but that it is not solely responsible for the observed differences. Our experiments provide the first unambiguous evidence for genetic divergence in shell morphology in an ongoing freshwater gastropod radiation in association with marked fitness differences among species under controlled habitat conditions. CONCLUSIONS: Our results indicate that differences in shell morphology among Lanistes species occupying different habitats have an adaptive value. These results also facilitate an accurate reinterpretation of morphological variation in fossil Lanistes radiations, and thus macroevolutionary dynamics. Finally, our work testifies that the shells of freshwater gastropods may retain signatures of adaptation at low taxonomic levels, beyond representing an evolutionary novelty responsible for much of the diversity and disparity in mollusks altogether.